Aloe vera Extract Sheet and Egg Albumin (Gallus domesticus) Reduce the Number of Lymphocytes on Gingival Incision Wound - Wizni A'dila A'ziza; Christiana Cahyani Prihastuti; Mutia Rochmawati; Alya Ghina Rosyada; Myrna Evana Amanda Putri (Jurnal Kedokteran Brawijaya, 2023)
An incision in the oral cavity is a dental procedure performed in surgical procedures. Suturing is the gold standard in primary wound closure care, however, suturing can cause tissue trauma, scars, and secondary infections. Cyanoacrylate adhesive is one of the alternative tissue glue for wound closure but it has inflammatory risk as suturing, potential toxicity, and accidental adhesion risks. Aloe vera extract sheet based combined with free-range chicken egg albumin is expected to be an alternative method for wound healing of gingival incisions. This study aimed to investigate the effect of administration of Aloe vera extract wound healing sheet (WHS) and free-range chicken egg albumin on the number of lymphocytes in the gingival incision wound as the inflammatory response. Experimental laboratory research with a posttest-only control group design was conducted in 24 male rats (Rattus norvegicus Wistar strain) with an incised gingiva, divided into four groups, namely T1 (50% WHS concentration and chicken egg albumin), T2 (100% WHS concentration and chicken egg albumin), PC (positive control with suturing), NC (negative control without treatment). The treatment was carried out for seven days. The data obtained were analyzed statistically using One-way ANOVA and Post Hoc LSD. The use of Aloe vera extract WHS and free-range chicken egg albumin (T1 and T2) reduced the number of lymphocytes compared to control groups (PC and NC; p<0.05). WHS and chicken egg albumin can shorten the inflammatory process in wound healing which is characterized by lower lymphocyte counts compared to the control groups.